Far as the eye can see : a novel - Bausch, Robert (Bloomsbury USA, 2014)
Civil War veteran Bobby Hale journeys into the Plains Wars-stricken American West, discovering a sense of purpose through his encounters with Native Americans and settlers who scrabble for peace and survival.